(untitled) (Journal of Hama University, 2020)
Temporomandibular Joint Disorders (TMD’s) have been one of the most common problems in societies. Many treatment methods were used like occlusal splints, physical treatment, hyaluronic acid, and ultrasonic treatment. Different theories studied causes and treatment methods of anterior disk displacement with reduction (ADD). Lateral pterygoid muscle spasm is one of the oldest given theories. It’s well known the Botulinum toxin type /A/ affection on muscles, and it has been used before in TMJ recurrent dislocation. The aim of this study is to evaluate the efficiency of Botulinum toxin injection in the lateral pterygoid muscle for restricting the muscle spasm and improving the symptoms and disc-condyle relation.The study took place at Department of Oral and Maxillofacial Surgery at Tishreen university hospital.The research sample included 10 patients, there ages were around 20 – 30 years old. We confirmed the diagnosis with MRI and compare it with another images after 6 months. We applied 35 units of botulinum toxin injections in the superior lateral pterygoid muscle following the external way according Brin. Within the context of this study after a six month follow up it was revealed that Botulinum Toxin A on which was applied has improved the pain sensor in the cases. There was considerable improvement in chewing efficacy and reduction of the density of TMJ sounds.The use of Botulinum Toxin A has indicated a considerable success on the treated patients, and stabile improvement during the observation period.